Pengabdian Kepada Masyarakat Pada Pelaksanaan Pekerjaan Pengaspalan Jalan Pada Proyek Rekonstruksi Dan Rehabilitasi Jalan Lumpangi–Loksado - Misnawati Misnawati; Elva Shanty Widuri; Pahrianoor Pahrianoor; Hanafi Gobek; Helda Aulia Rahimah; Raudatul Zakiah (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This Community Service (PkM) activity aims to increase public understanding of the implementation of road pavement work in the Lumpangi-Loksado Road Reconstruction and Rehabilitation Project, South Hulu Sungai Regency. This program is motivated by the importance of increasing public knowledge of the stages of road construction, the use of materials and equipment, quality control, and work safety so that it can support the success of infrastructure development and increase community participation in maintaining roads that have been built. The implementation method uses a participatory, technical, and collaborative approach through field observation, material delivery, technical assistance, discussion, documentation, and evaluation. The results of the activity show that the community has gained a better understanding of the stages of road pavement work according to technical standards, the importance of using the right working methods, the function of construction equipment, and quality control to produce strong, safe, and comfortable roads. In addition, this activity increases public awareness of the importance of maintaining road infrastructure to support the sustainability of road functions as a means of transportation. The implementation of the reconstruction and rehabilitation of the Lumpangi-Loksado Road also provides benefits in improving accessibility, mobility, road user safety, and supporting economic and tourism activities in the region.